The Influence of Organizational Culture, Organizational Commitment, and Motivation on Organizational Performance (Case Study: BEM And MCC Solo Technology Christian University) - Ayu Andira Wulandari; Adhita Maharani Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Good organizational performance can be produced with various supporting factors, such as culture, commitment, and motivation. The purpose of this study was to determine and analyze the influence of organizational culture, organizational commitment, and motivation on organizational performance at Universitas Kristen Teknologi Solo. The population that the researchers made the object of research was the Organization Management at Solo Christian University of Technology for the 2020-2022 period. The sample acquisition in this study uses certain criteria or called purposive sampling. The data used in this study were primary data and secondary data, while the data collection technique used questionnaires processed using SPSS. The results of this study show that Organizational Culture, Organizational Commitment, and Motivation partially affect Organizational Performance. Simultaneously the results of research on Organizational Culture, Organizational Commitment, and Motivation affect Organic Performance.